Looking Islam in the Teeth: The Social Life of a Somali Toothbrush. (14th April 2015) - Laird, Lance D.; Barnes, Linda L.; Hunter‐Adams, Jo; Cochran, Jennifer; Geltman, Paul L.
<x xml:space="preserve">Abstract</x> The Arabic miswak (Somali, adayge) is a tooth‐cleaning stick from the Salvadora persica plant. In this article, we trace the social life of a "thing, " examining meanings inscribed in the stick brush, drawing on interviews with 82 Somali refugees in Massachusetts and an analysis of local and transnational science and marketing. The miswak toothbrush symbolizes relationships to nature, homeland culture, global Islam, globalizing dental medicine, and the divine as it intersects with the lives of producers, marketers, distributors, and users, creating hybrid cultural forms in new contexts.